"LO QUE SE HABLABA DE ÉL Y LA ESCANDALOSA VIDA QUE ESTABA DANDO AL PÚBLICO" AN APPROACH TO THE CONCEPT OF SCANDAL BASED ON THE EFFECTS OF RUMOR ON INFORMAL AGREEMENT PRACTICES. THE CASE OF DON JOSÉ TADEO ALQUIZAR WHO LIVED "OUTRAGEONSLY" WHIT A "MULATA". - Celis Valderrama, Nicolás (Revista de Historia Social y de las Mentalidades, 2016)
This paper intends to provide an analysis of the  concept of scandal in Chile by the end of the  x VIII century, based on the impact of “rumor”  on Informal Agreement Practices. The concept  of scandal is presented as a phenomenon made  up from and within the public eye. In the same  way, this work describes the effects of rumor  and the importance of Informal Agreements as a  mechanism to control outrageous behavior. This  will be analyzed through the incident of Don  José Tadeo Alquizar who was living outrageously  with a “mulata”, in Santiago de Chile, 1795.
Keywords: Public scandal; Informal Agreement; Rumor; Public eye